Analysis of expression of candidate genes for polycystic ovary syndrome in adult and fetal human and fetal bovine ovaries. Issue 4 (17th July 2020) - Liu, Menghe; Hummitzsch, Katja; Hartanti, Monica D; Rosario, Roseanne; Bastian, Nicole A; Hatzirodos, Nicholas; Bonner, Wendy M; Irving-Rodgers, Helen F; Laven, Joop S E; Anderson, Richard A; Rodgers, Raymond J
Abstract: Polycystic ovary syndrome (PCOS) appears to have a genetic predisposition and a fetal origin. We compared the expression levels of 25 PCOS candidate genes from adult control and PCOS human ovaries ( n  = 16) using microarrays. Only one gene was potentially statistically different. Using qRT-PCR, expression of PCOS candidate genes was examined in bovine fetal ovaries from early stages when they first developed stroma through to completion of development ( n  = 27; 60–270 days of gestation). The levels of ERBB3 mRNA negatively correlated with gestational age but positively with HMGA2, FBN3, TOX3, GATA4, and DENND1A.X1, 2, 3, 4, previously identified as correlated with each other and expressed early. PLGRKT and ZBTB16, and less so IRF1, were also correlated with AMH, FSHR, AR, INSR, and TGFB1I1, previously identified as correlated with each other and expressed late. ARL14EP, FDFT1, NEIL2, and MAPRE1 were expressed across gestation and not correlated with gestational age as shown previously for THADA, ERBB4, RAD50, C8H9orf3, YAP1, RAB5B, SUOX, and KRR1. LHCGR, because of its unusual bimodal expression pattern, had some unusual correlations with other genes. In human ovaries ( n  = 15; <150 days of gestation), ERBB3.V1 and ERBB3.VS were expressed and correlated negatively with gestational age and positively with FBN3, HMGA2, DENND1A.V1, 3, 4, DENND1A.V1-7, GATA4, and FSHR, previously identified as correlated with each other and expressed early. Thus, the general lack of differential expression of candidate genes in adult ovaries contrasting with dynamic patterns of gene expression in fetal ovaries is consistent with a vulnerability to disturbance in the fetal ovary that may underpin development of PCOS. Abstract : Many PCOS candidate genes are expressed in fetal ovaries in one of three patterns either early, late or across gestation and within these groups, particularly the early and late, the levels of gene expression are correlated with each other.